Strategi Pemasaran Untuk Meningkatkan Volume Penjualan Kain Tenun Tradisional Mamasa pada Kelompok Usaha Kain Tenun Kreatif Pambe Kabupaten Mamasa - Selma, Jane; Stefani Marina Palimbong; Abedneigo Carter Rambulangi (ITB AAS Indonesia Surakarta, 2025)
This study aims to design marketing strategies to increase the sales volume of Mamasa traditional woven fabrics in the Kreatif Pambe Weaving Group, Mamasa Regency. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation studies. SWOT analysis is used to identify the group's strengths, weaknesses, opportunities, and threats. The findings indicate that the main strengths lie in product quality and unique weaving motifs, while the weaknesses include limited digital marketing and market access. Opportunities arise from the growing public interest in culturally based products, whereas threats come from competition with modern textile products. The recommended marketing strategy focuses on developing the marketing mix (7P), emphasizing product diversification, competitive pricing, digital marketing optimization, and marketing training for artisans. Implementing this strategy is expected to enhance competitiveness and expand the market for Mamasa woven fabrics. Keywords: Marketing strategy, Woven fabric, SWOT analysis, Marketing mix